Autism spectrum disorders in gender dysphoric children and adolescents. - de Vries ALC; Noens ILJ; Cohen-Kettenis PT; van Berckelaer-Onnes IA; Doreleijers TA (Journal of Autism & Developmental Disorders, 2010)
Only case reports have described the co-occurrence of gender identity disorder (GID) and autism spectrum disorders (ASD). This study examined this co-occurrence using a systematic approach. Children and adolescents (115 boys and 89 girls, mean age 10.8, SD = 3.58) referred to a gender identity clinic received a standardized assessment during which a GID diagnosis was made and ASD suspected cases were identified. The Dutch version of the Diagnostic Interview for Social and Communication Disorders (10th rev., DISCO-10) was administered to ascertain ASD classifications. The incidence of ASD in this sample of children and adolescents was 7.8% ( n = 16). Clinicians should be aware of co-occurring ASD and GID and the challenges it generates in clinical management.